2022
DOI: 10.1155/2022/1139587
|View full text |Cite
|
Sign up to set email alerts
|

SegChaNet: A Novel Model for Lung Cancer Segmentation in CT Scans

Abstract: Accurate lung tumor identification is crucial for radiation treatment planning. Due to the low contrast of the lung tumor in computed tomography (CT) images, segmentation of the tumor in CT images is challenging. This paper effectively integrates the U-Net with the channel attention module (CAM) to segment the malignant lung area from the surrounding chest region. The SegChaNet method encodes CT slices of the input lung into feature maps utilizing the trail of encoders. Finally, we explicitly developed a multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 46 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Similarly, Nasser and Naser [ 27 ] detected lung cancer using an artificial neural network (ANN) with a high accuracy of 96.67%. Cifci et al [ 28 ], the suggested Deep Learning with Instantaneously Trained Neural Networks (DITNN) method, coupled with the enhanced profuse clustering technique (IPCT), managed to improve lung image quality and the diagnosis rate of lung cancer with 98.42% accuracy. With an accuracy performance of 0.909 and 0.872, respectively, the paper in [ 29 ] suggested a double convolutional deep neural network (CDNN) and a conventional CDNN to recognize and classify lung nodules.…”
Section: Computer-assisted Lung Cancer Detection Using Ct Imagesmentioning
confidence: 99%
“…Similarly, Nasser and Naser [ 27 ] detected lung cancer using an artificial neural network (ANN) with a high accuracy of 96.67%. Cifci et al [ 28 ], the suggested Deep Learning with Instantaneously Trained Neural Networks (DITNN) method, coupled with the enhanced profuse clustering technique (IPCT), managed to improve lung image quality and the diagnosis rate of lung cancer with 98.42% accuracy. With an accuracy performance of 0.909 and 0.872, respectively, the paper in [ 29 ] suggested a double convolutional deep neural network (CDNN) and a conventional CDNN to recognize and classify lung nodules.…”
Section: Computer-assisted Lung Cancer Detection Using Ct Imagesmentioning
confidence: 99%
“…In this study, for the COVID-19 predictions, we used the available data for research purposes online [36][37][38][39][40][41]. From different countries' data from the date 11 March 2020-29 March 2020, we used different Python modules to visualize and describe the data and then trained ML time series models with 80% of data and tested on 20% of data.…”
Section: Design Of the Predictive Models And Experimental Setupmentioning
confidence: 99%
“…Therefore, early-stage detection can lead to better treatment for the patient and avert the spread of cancer at the right time, leading to an increase in the survival rate (6) . Doctors can benefit significantly from a wealth of imaging data to interpret lesions (7) accurately. Multi-parameter Magnetic Resonance Imaging (Mp-MRI), which consists of diffusion-weighted imaging (DWI), KTrans imaging, and dynamic contrast-enhanced imaging (DCE).…”
Section: Introductionmentioning
confidence: 99%